Strategi Penanganan Coronavirus Disease (Covid-19) Tahun 2020-2022 - Fernanda, Afridika (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
The purpose of this research is to understand how the government responded to the rapid increase of COVID-19 cases that began in March 2020. The research method used is field research with a historical approach, supported by primary and secondary data. The findings show that several policies were implemented, such as the establishment of the COVID-19 Task Force, enforcement of social distancing, and restrictions on public activities. Community participation was also an essential factor in the effectiveness of these policies. The conclusion of this study emphasizes that sustainable public health education, cooperation among stakeholders, and consistent adherence to health protocols are crucial in overcoming pandemics and preparing for future public health crises. Keywords: COVID-19, Health Protocols, Historical Analysis, Pandemic Response, Public Health.